PERAN SAKTI PEKSOS DALAM MENDAMPINGI ANAK-ANAK TERLANTAR (SUDUT PANDANG TEORI SOCIAL LEARNING) DI DINAS SOSIAL KABUPATEN GUNUNG KIDUL - Vikri Rahmaddani (Masyarakat Madani: Jurnal Kajian Islam dan Pengembangan Masyarakat, 2018)
Child social welfare can be fulfilled with Child Social Welfare Program (PKSA), which this program has been implemented by social office of GunungKidul regency which in its implementation can not be separated from the role of a social worker. In this child social welfare program does not separate the child from the family, but the child lives with the family, so the model of accompaniment in doing social work from the social service is insindental (at any time) when needed to assist the client. The formulation of the problem is how the role of social work through Child Social Welfare Program (PKSA) which is implemented by the Social Service of GunungKidul Regency, and what are the social worker barriers in implementing Child Social Welfare Program (PKSA) implemented by Social Service of GunungKidul Regency In general, this study is a development of research through qualitative descriptive approach, to obtain an accurate process in conducting research on the role of Social Worker In Accompanying Neglected Children (Viewpoint of Social Learning Theory), the authors determine informants from relevant stakeholders, consisting of government in social offices or related institutions and Saktipeksos. In this study the authors determine the informants by purposive sampling technique, which means choosing a deliberately chosen informant who taknib because there are considerations to achieve certain goals. So they can provide the right input about the accompaniment in the process carried out. Methods of data collection used are interviews, observation, and documentation. After the data collected, the next step the authors determine the technique of data validation, while the selected technique is keajengan observation with the intention of finding the characteristics and elements in situations that are very relevant to the issues and issues sought, then focus than on those things detailed. With this the authors only make observations to the problem in the precise is the role of SaktiPeksos in assisting children abandoned with Social Learning Theory.